Comprehensive two-dimensional gas chromatography with time-of-flight mass spectrometric detection for the determination of anabolic steroids and related compounds in nutritional supplements - Štěpán, Radim; Cuhra, Petr; Baršová, Soňa (Food additives & contaminants. Part A, Chemistry, analysis, control, exposure & risk assessment, 2008)
A simple and effective analytical method for the determination of anabolic steroids and related compounds in nutritional supplements is reported. Target compounds are extracted with ethyl acetate, crude extract is purified using dispersive solid-phase extraction (SPE) with primary secondary amine (PSA) as sorbent, and finally they are identified and quantified as underivatized compounds using two-dimensional gas chromatography with time-of-flight mass spectrometric detection (GCxGC-TOF MS). This method was validated for 25 steroids in two types of commercially available solid nutritional supplements: protein concentrate and creatine monohydrate. Repeatability expressed as the relative standard deviation of analyte concentration ranged from 4.1 to 20.5%. Recoveries between 70.0 and 122.6% were obtained for the target compounds except for oxymetholone in protein concentrate where the recovery was low as a result of strong interactions with PSA. Excellent linearity was obtained for six-point calibration with regression coefficients of 0.997-1.000 for all compounds. The limits of quantification ranged from 0.007 to 0.114 mg kg(-1). For a monitoring programme of 48 samples of nutritional supplements, three were positive. Nandrolone, testosterone, dehydroepiandrosterone (DHEA), 5alpha-androstan-3,17-dione, 19-norandrostendione and progesterone were found in positive samples at concentrations between 0.022 and 0.398 mg kg(-1).
Keywords: Dietary Supplements; Gas Chromatography-Mass Spectrometry; Česká republika; Anabolic Agents; lidé; Reference Standards; referenční standardy; Doping in Sports; doping ve sportu; anabolika; Czech Republic; plynová chromatografie s hmotnostně spektrometrickou detekcí; potravní doplňky; Humans